Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

When we prove a function is an isomorphism, we need to prove it's a bijection and it's closed under an operation. In one example I had no problem proving the first part, but in the second part, I proved that $f^{-1}(ab)=f^{-1}(a)f^{-1}(b)$, so my question is does it also follow that $f(ab) = f(a)f(b)$?

share|cite|improve this question
up vote 2 down vote accepted

Using what you have already shown:$$ f^{-1}(f(a)f(b)) = f^{-1}(f(a)) f^{-1}(f(b)) = ab \\ f(a)f(b) = f(f^{-1}(f(a)f(b))) = f(ab) $$

share|cite|improve this answer

Yes write $a=f(a')$ and $b=f(b')$ then $$f^{-1}(ab)=f^{-1}(a)f^{-1}(b)\iff f^{-1}(f(a')f(b'))=a'b'\iff f(a')f(b')=f(a'b') $$

share|cite|improve this answer

Yes, a bijective homomorphism's inverse is also a homomorphism.

Also, it does not make sense to say that a function is closed under an operation. A function is compatible with an operation. A subset is closed under an operation.

share|cite|improve this answer

If it is true that $f^{-1}(ab)=f^{-1}(a)f^{-1}(b)$, then we have $$f(ab)=f^{-1}(f^{-1}(ab))=f^{-1}(f^{-1}(a)f^{-1}(b))=f^{-1}(f^{-1}(a))f^{-1}(f^{-1}(b))=f(a)f(b)$$

share|cite|improve this answer
if $f:E\to F$, $f^{-1}\circ f^{-1}$ is not defined – mookid Apr 13 '14 at 23:19

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.